EFFECTS OF RAREFIED GAS FLOW ON VELOCITY BOUNDARY AND TEMPERATURE CHARACTERISTICS OF AEROSTATIC GUIDE WAY - LONG Wei; GONG Ling; YANG ShaoHua (Jixie qiangdu)
When the thickness of aerostatic guide way gas film is in the scale of micron meters,the air flow inside is in the slip regime according to Kn. In this case,pressure distribution and bearing characteristics of the gas film will be influenced by rarefied effect. The most outstanding characteristics is shown as velocity slip and temperature jump. Based on LBM,velocity and temperature distribution in the radial direction can be achieved. Based on the study of a mathematical model and simulation analysis,with the increase of Kn,the degree of velocity slip increases. The result of velocity slip benefit cooling effectiveness,but the temperature jump is negative. This is because temperature jump acts as an additional thermal resistance between rail and air film,which is not beneficial to radiating of aerostatic guide way.